Beyond Joint Property? Examining Fiqh Munakahat, State Law, and Customary Practice in Aceh, Indonesia - Musfira Musfira; Putri Rahmah Nur Hakim; Khairani Mukdin; Irwan Abdullah; Syahrizal Abbas; Salmy Edawati Yaacob (USRATY : Journal of Islamic Family Law, 2026)
This study aims to reconstruct the concept of joint marital property in Aceh by examining how statutory law, Islamic jurisprudence, and customary law interact in the resolution of marital property disputes. Previous studies have largely examined joint marital property from a single legal perspective, particularly state law or Islamic family law, while insufficient attention has been given to how these normative systems interact in actual dispute resolution and shape the distribution of marital assets in Aceh. This study employs a qualitative socio-legal approach, combining normative legal analysis with empirical data from document analysis and semi-structured interviews with Religious Court judges, customary leaders, legal practitioners, and divorced spouses. The findings reveal three interconnected patterns: first, differences between statutory provisions, Islamic jurisprudence (fiqh munakahat), and customary norms produce divergent interpretations of ownership and distribution; second, village deliberation (musyawarah gampong) remains an important mechanism for resolving disputes before or alongside formal judicial processes; and third, Religious Court judges reconcile multiple legal sources by considering both normative rules and the social and economic circumstances of the spouses. The study concludes that joint marital property in Aceh functions within a plural legal order that requires greater normative and institutional harmonization. Accordingly, the study proposes an integrative reconstruction model that recognizes both spouses’ economic and domestic contributions as a basis for equitable property distribution. The model contributes to Islamic family law scholarship by strengthening legal certainty, gender justice, and the protection of spouses’ economic rights within Aceh’s plural legal system.